Measurement and Monitoring System for Agricultural Soil Environmental Parameters Based on the Internet of Things - Amir, Ashadi; Suwardoyo, Untung; Pratami Irwan, Irninthya Nanda (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
Measurement and monitoring of environmental parameters in agricultural soil are needed to understand the condition of agricultural land. The measurement of agricultural land is mostly still done manually, resulting in low accuracy levels, requiring significant time and effort, and not providing periodic measurement results. The variation in soil characteristics and the limitations of tools also hinder the effectiveness of measurements, making the use of modern technology increasingly important. In this research, a system has been designed to measure environmental parameters of agricultural soil in real-time. The designed system consists of soil moisture sensors and soil pH sensors integrated with the ESP32 microcontroller. The system comprises of two main parts: a sensor node that have functions to acquire sensor data and a web application that displays the measurement results. Initial testing was conducted by calibrating and validating data for each sensor used. Subsequent testing involved sending the measurement data of environmental parameters of agricultural soil to a database for display on an Internet of Things-based application. The test results showed that the agricultural soil was read as wet when the soil moisture sensor readings indicated values of 78–100%. For the pH sensor testing, the average error was found to be 5.67%.Pengukuran dam pemantauan parameter lingkungan tanah pertanian dibutuhkan untuk mengetahui kondisi tanah pertanian. Pengukuran tanah pertanian sebagian besar masih dilakukan secara manual sehingga tingkat akurasi pengukuran masih rendah, membutuhkan waktu dan tenaga yang besar dan tidak mendapatkan hasil pengukuran secara berkala. Variasi karakteristik tanah dan keterbatasan alat juga menghambat efektivitas pengukuran, sehingga penggunaan teknologi modern menjadi semakin penting. Pada penelitian ini dirancang sebuah sistem yang dapat melakukan pengukuran parameter lingkungan tanah pertanian secara real-time. Sistem yang dirancang terdiri dari sensor kelembaban tanah dan sensor pH tanah yang terintegrasi dengan perangkat mikrokontroler ESP32. Sistem terdiri dari dua bagian utama yaitu sensor node yang berfungsi untuk melakukan akuisisi data sensor dan aplikasi web yang berfungsi untuk menampilkan hasil pengukuran. Pengujian awal dilakukan dengan melakukan kalibrasi dan validasi data untuk setiap sensor yang digunakan. Pengujian selanjutnya dilakukan dengan menguji pengiriman data hasil pengukuran parameter lingkungan tanah pertanian ke database untuk ditampilkan pada aplikasi berbasis Internet of Things. Hasil pengujian menunjukkan bahwa tanah pertanian terbaca basah ketika hasil pembacaan sensor kelembaban tanah menunjukkan nilai 78 – 100%. Untuk pengujian sensor pH menghasilkan nilai error dengan rata-rata sebesar 5.67%.